Strategy and Function of Snow and Ice Movement on Economic Revitalization in Northeast China - Liu, Yaqi (Transactions on Economics, Business and Management Research, 2024)
This paper explores the strategic role of snow and ice sports in driving the economic revitalization of Northeast China. Leveraging the momentum from the 2022 Beijing Winter Olympics, the region's vast ice and snow resources offer new avenues for economic growth. Through a combination of literature review and case studies, the research demonstrates how snow and ice sports can advance the regional economy, stimulate rural revitalization, and refine industrial structures, thereby serving as a foundation for policy development. The study highlights that fully utilizing these natural resources and enhancing infrastructure are crucial for fostering the growth of the snow and ice industry. Additionally, it emphasizes the importance of integrating snow sports with regional economic plans, offering theoretical guidance for the development and enactment of policies. This research underscores the essential role of snow and ice sports in promoting sustainable economic progress in Northeast China and contributes valuable insights for future policy planning.